Evaluation of AERONET precipitable water vapor versus microwave radiometry, GPS, and radiosondes at ARM sites. Issue 15 (11th August 2014) - Pérez‐Ramírez, Daniel; Whiteman, David N.; Smirnov, Alexander; Lyamani, Hassan; Holben, Brent N.; Pinker, Rachel; Andrade, Marcos; Alados‐Arboledas, Lucas
Abstract In this paper we present comparisons of Aerosol Robotic Network (AERONET) precipitable water vapor (W) retrievals from Sun photometers versus radiosonde observations and other ground‐based retrieval techniques such as microwave radiometry (MWR) and GPS. The comparisons make use of the extensive measurements made within the U.S. Department of Energy Atmospheric Radiation Measurement Program (ARM), mainly at their permanent sites located at the Southern Great Plains (Oklahoma, U.S.), Nauru Islands, and Barrow (Alaska, U.S.). These places experience different types of weather which allows the comparison of W under different conditions. Radiosonde and microwave radiometry data were provided by the ARM program while the GPS data were obtained from the SOUMINET network. In general, W obtained by AERONET is lower than those obtained by MWR and GPS by 6.0–9.0% and 6.0–8.0%, respectively. The AERONET values are also lower by approximately 5% than those obtained from the numerous balloon‐borne radiosondes launched at the Southern Great Plains. These results point toward a consistent dry bias in the retrievals of W by AERONET of approximately 5–6% and a total estimated uncertainty of 12–15%. Differences with respect to MWR retrievals are a function of solar zenith angle pointing toward a possible bias in the MWR retrievals. Finally, the ability of AERONET precipitable water vapor retrievals to provide long‐term records of W in diverse climate regimes is demonstrated.